Latin American history goes to the movies : understanding Latin America's past through film - Brewer, Stewart, 1971- (Routledge, Taylor & Francis Group, 2024)
This new edition of Latin American History Goes to the Movies uses a variety of feature films as a method of studying key historical themes in Latin America, from pre-Columbian cultures to contemporary debates. The book provides historical context as a way of interpreting Latin American filmography, offering multiple classroom viewing options per chapter theme. Each chapter is dedicated to a central concept or issue, such as stereotypes, conquest and colonialism, revolution, religion, gender, and politics. The second edition includes four additional chapters on dictatorships, LGBTQIA+ issues, the environment, and Indigenous peoples. Twenty new films, including La Fiesta del Chivo, Fresa y Chocolate, Embrace of the Serpent, and Roma appear throughout this edition, presenting additional perspectives and updates for today's readers. The discussions of films and the history behind them offer a flexible and nuanced approach to understanding Latin American cultures, differentiating between stereotypical depictions and the realities of history. Concise and accessible, Latin American History Goes to the Movies is a unique resource for students and instructors in Latin American history and film studies to analyse developments in Latin America throughout previous centuries.